(3GdcfR aj GdbQGAGJ GdYTQs - (3YHO Gddg Hf YHO GdeDef GHf GdhLjg GdhGSWj, CHh eMeO,J (B740 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Pi GdYRI hGdYdGg hGdYXeI hGdHgGA hGdbOQI hGdcHQjGA GdeJaQO HOhGe GdHbGA GdhGMO GdCMO GdaQO GdUeO s
(3BNQgG (B:s
(3hai GdOjf di Ojf Jced fXegG HNeSjf HjJkG HYOgG NeSI s
(3GdfSNI HgG MhGTs
(3LeY ajg Hjf GdEQTGO ddbdGfSi hGdJjSQ ddOGfi hRGOg ahGFOs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1519s
Keywords: (3GdbQGAGJ hGdJLhjOs